An Assessment of Students’ Self-Regulated Learning of a Higher Education Institution in a Highly Urbanized City in the Philippines - De Manuel, Joanna Marie Pina (JPAIR Institutional Research, 2022)
Nowadays, learners have found various ways to learn individually through available technologies. Moreover, with the pandemic where flexible learning was implemented and a modular approach was utilized, the students had a hard time taking the initiative to study independently and setting goals in their academic endeavors. Students cannot manage the information they get; they have difficulties critically analyzing the important information they need. Thus, they should be properly guided on self-regulated learning since the curricula nowadays are student-centered. The study aimed to assess the self-regulated learning level of the 2nd-4th year students of the Pamantasan ng Lungsod ng Pasig in terms of planning, monitoring, controlling or adjusting, and reflecting. The study adopted the descriptive method with 2,302 respondents from the five colleges. Based on the findings, the students have a moderate level of self-regulated learning. Moreover, there is a significant difference in the self-regulated learning of the students when grouped according to their sex, age, college level, program, units enrolled, and weekly allowance. However, there is no significant difference in their self-regulated learning according to their academic status and scholarship. In addition, there is a significant relationship between the self-regulated learning level and academic performance of the student-respondents of PLPasig. It is recommended that students must be exposed to more complex, open-ended tasks that will make them practice managing distractions and maintaining focus while tackling increasingly challenging academic work.
Keywords: Education; self-regulated learning; descriptive method; Pasig City-Philippines